Modern studies democracy in Scotland and the UK - Cooney, Frank; Hughes, Gary; Sheerin, David (Dynamic learning, 2018)
This second edition comprehensively covers the changes made to course content and prepare students to cope with the increased emphasis on knowledge and understanding in the new National 5 exam. - Analyses what it means to live in a democracy - Defines representation in the Scottish and UK Parliaments - Explains voting systems and election campaigns in the UK